High Performance Work Practice (HPWP) Implementation at Pt. Sumoda Tama Berkah (“Mbok Darmi Milk”) In Bogor City, West Java - Hadiyat, Yayan; Herman, (Journal of Social Transformation and Regional Development, 2023)
The community service program is the university's commitment to carry out the functions of the Tri Darma of Higher Education in an integrated manner with the functions of education and research. The mentoring program for improving management systems in SMEs, namely PT. Sumoda Tama Berkah, which has a business in the food and beverage industry with the Trademark "Susu Mbok Darmi," takes the theme Implementation of High Performance Work Practices (HPWPs), which aims to build a strong foundation on three pillars: 1) Practices to improve employee capabilities, such as training and skills development; 2) Practices to increase employee motivation, such as structuring reward systems, career development, and information sharing through improving organizational communication skills; and 3) Practices that give employees the opportunity to go the extra work, such as employee engagement and teamwork. The program is implemented through training using problem-based learning and experiential training methods, as well as through direct consultation, assistance and mentoring. Strengthening the "Outside-in" mindset in the concept of Human Resource Business Partners (HRBP) is very important to provide ways to find arguments for customers, namely "value propositions", so that every employee understands the importance of providing a excellent service. Through training in the fields of HR, operation management and supply chain, communication skill and excellent service, and managerial skills training, it is expected to be able to provide a strong foundation for practicing HPWPs, which ultimately aim to improve company performance and corporate sustainability.